2021
DOI: 10.3389/fmars.2021.697179
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Mixing and Heat Fluxes Conditioned by a Seismically Imaged Oceanic Front

Abstract: The southwest Atlantic gyre connects several distinct water masses, which means that this oceanic region is characterized by a complex frontal system and enhanced water mass modification. Despite its significance, the distribution and variability of vertical mixing rates have yet to be determined for this system. Specifically, potential conditioning of mixing rates by frontal structures, in this location and elsewhere, is poorly understood. Here, we analyze vertical seismic (i.e., acoustic) sections from a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Commercial seismic records are thus likely to have higher signal-to-noise ratios and to be more accurately spatially positioned than records acquired for scientific research. Dense layouts of overlapping transects are often acquired in a small area over a period of several weeks or months, allowing the temporal evolution of oceanographic phenomena to be tracked (e.g., Dickinson et al, 2020;Gunn et al, 2020b;Zou et al, 2020;Gunn et al, 2021). Many commercial exploration vessels carry several parallel cables of hydrophones, enabling imaging of thermohaline structure in three spatial dimensions (these Black dot = repeatedly sampled point; black star = acoustic source at time t 0 ; solid black lines with arrows = travel path for sound waves excited at time t 0 and reflected from black dot; gray stars = acoustic source at later times t 1 , t 2 , t 3 ; dashed gray lines with arrows = travel paths for sound waves excited at times t 1 , t 2 , t 3 and reflected from black dot.…”
Section: Use Of Existing Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial seismic records are thus likely to have higher signal-to-noise ratios and to be more accurately spatially positioned than records acquired for scientific research. Dense layouts of overlapping transects are often acquired in a small area over a period of several weeks or months, allowing the temporal evolution of oceanographic phenomena to be tracked (e.g., Dickinson et al, 2020;Gunn et al, 2020b;Zou et al, 2020;Gunn et al, 2021). Many commercial exploration vessels carry several parallel cables of hydrophones, enabling imaging of thermohaline structure in three spatial dimensions (these Black dot = repeatedly sampled point; black star = acoustic source at time t 0 ; solid black lines with arrows = travel path for sound waves excited at time t 0 and reflected from black dot; gray stars = acoustic source at later times t 1 , t 2 , t 3 ; dashed gray lines with arrows = travel paths for sound waves excited at times t 1 , t 2 , t 3 and reflected from black dot.…”
Section: Use Of Existing Datasetsmentioning
confidence: 99%
“…The resolution of these records is highly variable, and it is unclear how well they capture activity in the subsurface ocean (Wunsch, 1997). Comparison of existing seismic oceanographic datasets to historical satellite records will demonstrate the extent to which sea-surface observations can predict motions at depth (e.g., Dickinson et al, 2020;Gunn et al, 2020b;Gunn et al, 2021;Wei et al, 2022). The next generation of satellite-borne altimeters and current meters is expected to achieve resolutions as low as ∼1 km (e.g., Gommenginger et al, 2019;Klein et al, 2019;Martıńez-Moreno et al, 2021).…”
Section: Submesoscale Currentsmentioning
confidence: 99%
“…Based on the assumption that seismic reflections are a reasonable approximation of isopycnal surfaces (Krahmann et al, 2009;Holbrook et al, 2013), studies have shown that turbulent diffusivity can be accurately measured from vertical displacement spectra of tracked reflections (e.g., Figure 3A) from both the internal wave subrange (Sheen et al, 2009;Dickinson et al, 2017) and turbulent subrange (Holbrook et al, 2013;Fortin et al, 2016;Mojica et al, 2018;Tang et al, 2019;Gunn et al, 2021). To clearly recognize the transition from internal wave regimes to turbulent regimes in log-log space, the vertical displacement spectra are multiplied by (2πk x ) 2 to produce the slope spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional hydrographic acquisition data, seismic images of the water column are distinguished by excellent vertical and horizontal resolutions of the order of 20 meters [23]. Up to now, seismic oceanography data have been used to investigate various oceanic phenomena with unprecedented horizontal resolutions in the global oceans, such as eddies [25][26][27], ocean fronts [22,28], internal waves and turbulent mixing [29][30][31][32][33]. Moreover, it is demonstrated that internal wave and turbulence regimes can be identified in the horizontal spectra of vertical displacements derived from seismic undulations [29,34].…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent dissipation rates, which are normally measured by microstructure profilers, are widely used to compute heat fluxes associated with seasonal sea ice [41], thermohaline staircases [42], environmental forcing factors [43], etc. Recently, by exploiting turbulent dissipation rates derived from seismic reflections, Gunn et al [28] estimated vertical heat fluxes due to the diapycnal mixing of a front in the Brazil-Falkland Confluence, demonstrating the possibility of estimating heat fluxes from seismic oceanographic data. However, when considering heat fluxes within a meddy, different mixing processes (e.g., diffusive convection, salt fingers and thermohaline intrusions) need to be accounted for separately.…”
Section: Introductionmentioning
confidence: 99%